The quality of life in papillary thyroid microcarcinoma patients undergoing lobectomy or total thyroidectomy: A cross‐sectional study - Yu Lan; Li Cao; Qing Song; Zhuang Jin; Jing Xiao; Lin Yan; Yukun Luo; Mingbo Zhang (Cancer Medicine, 2021)
Abstract Objective Papillary thyroid microcarcinoma (PTMC) has a good prognosis and a long survival time, surgery is the common treatment including total thyroidectomy (TT) and unilateral lobectomy (LT), but recent studies showed that TT does not show an advantage over LT for PTMC in preventing cancer recurrence and reducing mortality. Given this, the health‐related quality of life (HRQoL) has become one of the important factors that physicians must consider when making treatment decisions. The aim of this study was to compare the HRQoL of patients between undergoing TT and LT. Methods From October 2019 to December 2019, 69 PTMC patients were enrolled in our study, including 34 in the LT group and 35 in the TT group, respectively. We used three questionnaires which included the 36‐item short‐form health survey (SF‐36), thyroid cancer‐specific quality of life (THYCA‐QOL), and Fear of Progression Questionnaire‐Short Form (FoP‐Q‐SF) for each patient to evaluate their scores of HRQoL. Results According to the SF‐36, the scores of the domain for the role limitation due to physical problems, emotional problems, and social function (RP, RE, and SF) as well as Physical Component Summary (PCS) and Mental Component Summary (MCS) showed a significant negative linear association between the LT group and TT group: RP (coefficient [coef]: −33.953 [confidence interval (CI) −51.187 to −16.720], p < 0.001, RE (coef: −21.633 [CI −39.500 to −3.766], p = 0.018), SF (coef: −10.169 [CI −19.586 to −0.752], p = 0.035)and PCS (coef: −10.571 [CI −17.768 to −3.373], p = 0.005), MCS (coef: −10.694 [CI −19.465 to −1.923], p = 0.018). The THYCA‐QOL showed that the scores of the TT group were higher than that of the LT group in the problem of scar (coef: 16.245 [CI 1.697 to 30.794], p = 0.029 according to the multivariate analysis), suggesting a higher level of complaint in the TT group. There was no statistically significant difference in the scores of FoP‐Q‐SF between the two groups. Conclusions In patients with PTMC, LT offers an advantage over TT in terms of HRQoL, which supports the role of LT as an alternative strategy to TT.